2018
DOI: 10.1111/jnc.14296
|View full text |Cite
|
Sign up to set email alerts
|

Faim2 contributes to neuroprotection by erythropoietin in transient brain ischemia

Abstract: Delayed cell death in the penumbra region of acute ischemic stroke occurs through apoptotic mechanisms, making it amenable to therapeutic interventions. Fas/CD95 mediates apoptotic cell death in response to external stimuli. In mature neurons, Fas/CD95 signaling is modulated by Fas-apoptotic inhibitory molecule 2 (Faim2), which reduces cell death in animal models of stroke, meningitis, and Parkinson disease. Erythropoietin (EPO) has been studied as a therapeutic strategy in ischemic stroke. Erythropoietin stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 46 publications
(121 reference statements)
1
15
0
Order By: Relevance
“…In addition, gene expression of TMBIM3/GRINA is dysregulated in brains of patients with major depression [34] and in various cancers [35]. GRINA-deficiency is not lethal in fruit flies [29] and does not show a pathological phenotype in mice, consistent with the knockout of other TMBIM family members (FAIM2, TMBIM1 and TMBIM6) [30,33,36,37]. Mostly located at the ER membrane and inhibiting ER calcium release by inositol-1,4,5-trisphosphate receptors, GRINA might have a crucial role in diminishing ER stress.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, gene expression of TMBIM3/GRINA is dysregulated in brains of patients with major depression [34] and in various cancers [35]. GRINA-deficiency is not lethal in fruit flies [29] and does not show a pathological phenotype in mice, consistent with the knockout of other TMBIM family members (FAIM2, TMBIM1 and TMBIM6) [30,33,36,37]. Mostly located at the ER membrane and inhibiting ER calcium release by inositol-1,4,5-trisphosphate receptors, GRINA might have a crucial role in diminishing ER stress.…”
Section: Introductionmentioning
confidence: 95%
“…We reported previously that EPO secreted by astrocytes is protective for several brain cell types [21][22][23]. In addition, studies involving animal models have shown that EPO in the brain contributes significantly to neuroprotection [24][25][26][27]. Based on these data, we examined the effect of hypothermia on EPO expression in cultured astrocytes.…”
Section: Discussionmentioning
confidence: 98%
“…After the calculation with (5 timepoints × 6 gerbils/timepoint) – (5 timepoints)= 25, the number of 25 suggested the sample size in this experiment could be more than necessary, and six gerbils were used for each timepoint (Charan & Kantharia, 2013). Alternatively, we used G*Power with the select procedure using effect size from means (Komnig, Dagli, et al., 2018; Komnig, Gertz, et al., 2018) for further confirmation, which produced similar results. We firstly searched the papers dealing with ischemic preconditioning in the literature to calculate the sample size (A in Table S1).…”
Section: Methodsmentioning
confidence: 95%
“…However, we excluded gerbils with no significant ischemic injury of apoptosis and surviving cells in the CA1 area according to the ischemic period including 2 adult gerbils (1 in sham + 15‐min and 1 in 5 + 15‐min ischemia) and five middle‐aged gerbils (4 in sham + 15‐min and 1 in 5 + 15‐min ischemia) (Figure 1, C + D). Different from the previous studies (Komnig, Dagli, et al., 2018; Komnig, Gertz, et al., 2018) that included those animals died and had their samples lost or not well treated during experiments within the target of sample size, this study did not include any animals that died or had their samples lost or not well treated during experiments in our sample size calculation (Figure 1, C + D). The final number of six gerbils was reached for analysis at each time point in the four experimental groups with a final number of 72 in each adult and middle‐aged gerbil group.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation